Modification of macadamia nutshell for rapid removal of crystal violet from aqueous solution - Netshitandani Naledzani; Emmanuel Christopher Umejuru; Joshua N. Edokpayi (Results in Chemistry, 2025)
Water pollution caused by untreated industrial effluents is a significant environmental problem, posing severe risks to ecosystems and human health. In this study, modified macadamia nutshell (MMN) using 3 M HCl and H2O2 was used as an adsorbent to sequester crystal violet (CV) from aqueous solutions. The raw macadamia nutshell and MMN were characterized using several analytical techniques: Fourier Transform Infrared (FTIR) spectroscopy for functional groups, X-ray Diffraction (XRD) for crystallinity, Scanning Electron Microscopy (SEM) for surface morphology, and Brunauer-Emmett-Teller (BET) analysis for textural properties. Various experimental factors affecting CV adsorption were investigated, including contact time, dosage, pH, temperature, initial concentration, particle size, and water chemistry. The results showed that CV removal reached equilibrium within 5 min and remained nearly constant thereafter. The optimal dosage and pH for CV removal were 0.2 g and 4, respectively. Higher temperatures enhanced CV removal efficiency, while changes in water chemistry significantly influenced the sorption process. The adsorption process was best described by the Freundlich isotherm, and the kinetics followed a pseudo-second-order model. The positive enthalpy change indicated an endothermic process, and spontaneity was confirmed by negative change in Gibb's energy values. MMN demonstrated the ability to be regenerated and reused multiple times, making it a cost-effective and sustainable adsorbent.